A grooved porous hydroxyapatite scaffold induces osteogenic differentiation via regulation of PKA activity by upregulating miR‐129‐5p expression. (12th October 2022) - Deng, Li; Li, Xinlun; Ren, Xiaohua; Lai, Shuang; Zhu, Yushu; Li, Jing; Huang, Hao; Mu, Yandong
Abstract: Background and objective: Hydroxyapatite scaffolds with different morphologies have been widely used in bone tissue engineering. Moreover, microRNAs (miRNAs) have been proven to be extensively involved in regulating bone regeneration. We developed grooved porous hydroxyapatite (HAG) scaffolds with good osteogenic efficiency. However, little is known about the role of miRNAs in HAG scaffold‐mediated promotion of bone regeneration. The objective of this study was to reveal the mechanism from the perspective of differential miRNA expression. Methods: Scanning electron microscopy (SEM) was used to perform the coculture of cells and scaffolds. The miRNA profiles were generated by a microarray assay. A synthetic miR‐129‐5p mimic and inhibitor were used for overexpression or inhibition. The expression of osteogenic marker mRNAs and proteins was detected by quantitative real‐time PCR (qRT–PCR), Western blotting, and immunofluorescence. An ALP activity kit and alizarin red staining (ARS) were used to measure ALP activity and mineral deposition formation. Cell migration ability was examined by wound healing and transwell assays. Protein kinase A (PKA) activity was measured by enzyme‐linked immunosorbent assay (ELISA) after miR‐129‐5p transfection. Target genes were identified by a dual‐luciferase reporter assay. H89 preculture evaluated the cross talk between miR‐129‐5p and PKA activity. Heterotopic implantation models, hematoxylin–eosin (HE), immunohistochemistry staining, and micro‐CT were used to evaluate miR‐129‐5p osteogenesis in vivo. Results: miRNAs were differentially expressed during osteogenic differentiation induced by HAG in vitro and in vivo. miR‐129‐5p was the only highly expressed miRNA both in vitro and in vivo. miR‐129‐5p overexpression promoted osteoblast differentiation and cell migration, while its inhibition weakened the effect of HAG. Moreover, miR‐129‐5p activated PKA to regulate the phosphorylation of β‐catenin and cAMP‐response element binding protein (CREB) by inhibiting cAMP‐dependent protein kinase inhibitor alpha (Pkia). H89 prevented the effects of miR‐129‐5p on osteogenic differentiation and cell migration. HE, immunohistochemistry staining and micro‐CT results showed that miR‐129‐5p promoted in vivo osteogenesis of the HAG scaffold. Conclusion: The HAG scaffold activates Pka by upregulating miR‐129‐5p and inhibiting Pkia, resulting in CREB‐dependent transcriptional activation and accumulation of β‐catenin and promoting osteogenic marker expression.